2009
DOI: 10.1590/s0074-02762009000800020
|View full text |Cite
|
Sign up to set email alerts
|

Association of Lutzomyia longipalpis (Diptera: Psychodidae) population density with climate variables in Montes Claros, an area of American visceral leishmaniasis transmission in the state of Minas Gerais, Brazil

Abstract: In the present paper, we evaluate the relationship between climate variables and population density of Lutzomyia longipalpis in Montes Claros, an area of active transmission of American visceral leishmaniasis (AVL) mate cycle. L. longipalpis specimens from the 3-day captures each month in all trapping sites (independently of district, transmission profile or house location) were combined and the sum was taken as representative of the number of L. longipalpis captured in the respective month. The trapping si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
16
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 12 publications
8
16
1
2
Order By: Relevance
“…Epidemiologically speaking, this also suggests a precocious proximity of humans to the disease vector in our environment 5 , a finding that corroborates the study of Monteiro et al 17 , who observed that L. longipalpis was the prevalent species in both intradomiciles and peridomiciles during an entomologic survey in the municipality. Another important factor observed by these authors was that the population density of L. longipalpis in the local area might be associated with local climate variables (accumulated rainfall, average temperature, and relative humidity of air) 28 . In this study, more male individuals (64%) were affected by VL, which is compatible with the average of 61% found in the country.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Epidemiologically speaking, this also suggests a precocious proximity of humans to the disease vector in our environment 5 , a finding that corroborates the study of Monteiro et al 17 , who observed that L. longipalpis was the prevalent species in both intradomiciles and peridomiciles during an entomologic survey in the municipality. Another important factor observed by these authors was that the population density of L. longipalpis in the local area might be associated with local climate variables (accumulated rainfall, average temperature, and relative humidity of air) 28 . In this study, more male individuals (64%) were affected by VL, which is compatible with the average of 61% found in the country.…”
Section: Discussionmentioning
confidence: 96%
“…Additionally, the increased incidence of dengue in the municipality has led health authorities to give priority to measures designed to address this disease, to the detriment of the planned activities for VL control. According to the Ministry of Health 17,28 , and the data obtained are being used in the ongoing program of activities.…”
Section: Discussionmentioning
confidence: 99%
“…Entretanto, estudos realizados no Brasil geraram resultados inconsistentes sobre a relação entre temperatura e abundância de L. longipalpis. Há estudos encontrando relação direta 29 , relação inversa 30 , ausência de associação 31,32 e mesmo relações direta e inversa em diferentes sítios amostrais num mesmo município 33 . Dentre os diversos possíveis motivos para tais discrepâncias destacam-se a dependência de flebotomíneos de outras variáveis climáticas, como umidade, que, por sua vez, também pode se correlacionar com temperatura, diferenças nos microambientes estudados e no tipo de método estatístico utilizado para analisar os dados 28 .…”
Section: Campo Térmico Da Superfície Do Solounclassified
“…Topographic relief is an important factor in climate differences, especially in intertropical zones where there are different climate plateaus depending on altitude [17,24]. The results confirmed that sandflies fauna fell into two populations, with differences in composition and structure, between the two Parish that divided geopolitically the Municipality, perhaps motivated to that these two areas are ecologically different.…”
Section: Discussionmentioning
confidence: 72%
“…Zorilla et al correlated the presence of cutaneous leishmaniasis to environmental and socioeconomic variables in population of Yaucano Valley in Perú, the adaptability of sandflies to the human en vironment may lead to an increase in the number of leish maniasis cases [15]. However, studies in dry climate regions have presented controversial results, such as a lack of correlation between climate variables and sandflies density [16,17]. Temperature increases may also affect sandflies populations [18][19][20].…”
mentioning
confidence: 99%